2017
DOI: 10.5709/acp-0211-0
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Negative and Positive Interpersonal Interactions. What is the Relationship Between Central (EEG, fNIRS) and Peripheral (Autonomic) Neurophysiological Responses?

Abstract: in Affective and social neuroscience, catholic University of the sacred heart, Milan, italy 2 department of Psychology, catholic University of the sacred heart, Milan, italy interpersonal empathy, positive/negative interactions, fnirs, brain oscillations; autonomic activity emotional empathy is crucial to understand how we respond to interpersonal positive or negative situations. in the present research, we aim at identifying the neural networks and the autonomic responsiveness underlying the human ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 108 publications
(131 reference statements)
6
35
0
Order By: Relevance
“…Common method bias is due to the same data source or the rater, the same measurement environment or the same project context, or the artificial covariation caused by the predicted variables and calibration variables with the characteristics of the project. This kind of covariation was a systematic error, which could cause serious interference in the research results [30]. According to the single factor test of Hurman [30], the result of data fitting index made by structural equation model analysis was that χ2/df =2.319, NFI =0.897, CFI =0.938, RMSEA =0.064, which showed that this study does not include serious common method bias.…”
Section: Common Methods Bias Testmentioning
confidence: 81%
See 2 more Smart Citations
“…Common method bias is due to the same data source or the rater, the same measurement environment or the same project context, or the artificial covariation caused by the predicted variables and calibration variables with the characteristics of the project. This kind of covariation was a systematic error, which could cause serious interference in the research results [30]. According to the single factor test of Hurman [30], the result of data fitting index made by structural equation model analysis was that χ2/df =2.319, NFI =0.897, CFI =0.938, RMSEA =0.064, which showed that this study does not include serious common method bias.…”
Section: Common Methods Bias Testmentioning
confidence: 81%
“…This kind of covariation was a systematic error, which could cause serious interference in the research results [30]. According to the single factor test of Hurman [30], the result of data fitting index made by structural equation model analysis was that χ2/df =2.319, NFI =0.897, CFI =0.938, RMSEA =0.064, which showed that this study does not include serious common method bias.…”
Section: Common Methods Bias Testmentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, as demonstrated by previous studies [60,75], theta and delta modulations were considered as specific markers of motivational and emotional components of the subjects' engagement. In particular, greater activation in the delta band can be attributed to the fact that the latter represents a significant indicator of emotional behavior, cognition and social skills [56,76]. Moreover, delta activity results to be involved in motivational systems and emotional salience detection [60].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Al-Shargie et al found a significant improvement of stress detection when combining fNIRS and EEG 31 . Further, results of another study show that both signals correlate intrinsically, especially for low-frequency theta and delta bands 32 . Assessing fNIRS and EEG provides an immense advantage compared to fMRI in regard to insensitivity to movement artifacts and electrical noise 33 35 .…”
Section: Introductionmentioning
confidence: 91%